(3LhGH cJGH GdSGOIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3dh cGfJ GdCOhGJ JHdZ GdEQGOGJ CWGd Gdehdi HbGA GdSGOI GdENhGf GdeJeScjf HWGYI Gdhdi GdOjGf s
(3BNQgG (B:s
(3hbO VGb GdReGf Yf GdecGJHI hGdLhGH hGfbWY dMOJg Gdbhd hGdNWGH JeJ HMeO Gddg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B89s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis